PERANAN CUSTOMER SERVICE DALAM MENINGKATKAN CITRA PERUSAHAAN DI MATA NASABAH BANK MANDIRI KANTOR CABANG PEMBANTU SEPANJANG SIDOARJO - Basofi, Achmad; Tjahjono, Endro; Murti, Indah (Universitas 17 Agustus 1945 Surabaya, 2017)
The rapid growth in banking impact on the more intense competition in the case get customeror maintain a customer. Many similarities in terms of the program and products offered by the bank tothe customer make competition shifted toward corporate image banking. No exception The BankMandiri branch office of Sepanjang Sidoarjo who took the initiative demanding the customer serviceto replace the role of public relation in the increases image of the company but in portion of thedifferent. In this study researchers want to know the role of customer service Bank Mandiri branchoffice of Sepanjang Sidoarjo increases corporate image to customers. This study guide Bank Mandiribranch office of Sepanjang Sidoarjo and in process of data collection using interview, observation,and documentation. After data collected reseachers using the analysis of inductive to analyze and thenpresented in writing. The results prove a variety of the role of customer service increases corporateimage through serve with a vengeance, patience, fast response, friendly, polite, as well as alwaysprovide information updated to all customers. All of this prove that the role of customer serviceincreases image Bank Mandiri branch office of Sepanjang it is important. Recommendations in thisstudy is that the company continue to develop competence customer service to better again, and forfurther research in to include a wider again.Keywords : customer service, bank, image, customer